Analisis Indeks Workabilitas pada Campuran Asphalt Concrete dengan Asbuton B 50/30 - Indradewa Andrianto Putra; Ary Setyawan; Djoko Sarwono (Pusat riset dan Inovasi Nasional, 2023)
The majority of road construction in Indonesia uses flexible pavement, namely Asphalt Concrete (AC). Therefore, to meet the need for asphalt, Asbuton was carried out. This research aims to determine the effect of Asbuton content, mixing temperature, and compaction temperature on the workability index value. Therefore, research was carried out regarding the workability of the AC-WC mixture with Asbuton B 50/30 The preparation of test objects was carried out using the dry mixing method. The Asbuton content used was 10% and 15% and the mixing temperature was varied, namely 160⁰ C, 170⁰ C, 180⁰ C 190⁰ C, and 200⁰ C and the compaction temperature was 110⁰ C, 120⁰ C, 130⁰ C, 140⁰ C, and 150⁰ C at the level optimum asphalt. Then, the data obtained is processed using a statistical approach. The research results showed that the AC-WC mixture with 10% Asbuton content and varying mixing and compaction temperatures had a workability index value from 2.9890 to 5.7737. Meanwhile, the AC-WC mixture with 15% Asbuton content and varying mixing and compaction temperatures has a workability index value ranging from 3.3252 to 6.9845. This shows that variations in Asbuton content, mixing temperature and compaction temperature influence the workability index value of the AC-WC mixture.